2021
DOI: 10.1037/xlm0000997
|View full text |Cite
|
Sign up to set email alerts
|

On the limits of shared syntactic representations: When word order variation blocks priming between an artificial language and Dutch.

Abstract: Several studies used artificial language (AL) learning paradigms to investigate structural priming between languages in early phases of learning. The presence of such priming would indicate that syntactic representations are shared across these languages. found similar priming between Dutch (SVO order) and an AL with either SVO or SOV order. However, it is unclear whether such sharing would occur if the AL allows both the same and different word order as the native language. Indeed, the presence of a (easy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 55 publications
2
19
0
2
Order By: Relevance
“…This lowers the threshold to compute the dispreferred interpretation of the target sentences, leading participants to alternate between both target interpretations. Once this bias for a particular interpretation of the target sentence is lowered sufficiently, priming may emerge both within and between quantifiers (as previously hypothesised in a study on syntactic priming Muylle et al, 2021).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…This lowers the threshold to compute the dispreferred interpretation of the target sentences, leading participants to alternate between both target interpretations. Once this bias for a particular interpretation of the target sentence is lowered sufficiently, priming may emerge both within and between quantifiers (as previously hypothesised in a study on syntactic priming Muylle et al, 2021).…”
Section: Discussionmentioning
confidence: 83%
“…Experiments 3-4 aimed to identify the influence of experimental design. Experiment 3 tested whether priming between quantifiers depends on the presence of a within-quantifier condition (inspired by Muylle et al, 2021). This experiment revealed that priming between quantifiers emerges in experimental contexts without a within-quantifier condition but with multiple between-quantifier conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same effect holds in bilingual language processing, when the prime is presented in one language and the response is given in another language. An important caveat here, however, is that priming seems to be less effective when word order is not shared across the two languages (e.g., Bernolet, Hartsuiker & Pickering, 2007;Hartsuiker et al, 2004;Jacob, Katsika, Family & Allen, 2017;Loebell & Bock, 2003;Muylle, Bernolet & Hartsuiker, 2021). Cross-language priming effects constitute important evidence that similar syntactic representations in a bilingual's two languages are simultaneously activated and can influence each other, and, conversely, that cross-language activation is reduced during the processing of language-specific syntactic representations.…”
Section: Word Order Constraints In Code-switchingmentioning
confidence: 94%